Functional Annotation of 2D Protein Maps: The GelMap Portal - Braun, Hans-Peter; Senkler, Michael (Frontiers in Plant Science, 2012)
In classical proteome analyses, final experimental data are (a) images of 2D protein separations obtained by gel electrophoresis and (b) corresponding lists of proteins which were identified by mass spectrometry (MS). For data annotation, software tools were developed which allow to link protein identity data directly to 2D gels (“clickable gels”). GelMap is a new online software tool to annotate 2D protein maps. It allows (i) functional annotation of all identified proteins according to biological categories defined by the user, e.g. subcellular localization, metabolic pathway, or assignment to a protein complex and (ii) annotation of several proteins per analyzed protein “spot” according to MS primary data. Options to differentially display proteins of functional categories offer new opportunities for data evaluation. For instance, if used for the annotation of 2D Blue native / SDS gels, GelMap allows identifying protein complexes of low abundance. A web portal has been established for presentation and evaluation of protein identity data related to 2D gels and is freely accessible at http://www.gelmap.de/.